Synchronization of Autonomic and Cerebral Rhythms During Listening to Music: Effects of Tempo and Cognition of Songs - Mollakazemi, M J; Biswal, D; Elayi, S C; Thyagarajan, S; Evans, J (Physiological research, 2019)
A large number of studies document cardiorespiratory changes occurring while listening to music. Less is known, however, about the interaction between cardiorespiratory and cerebral electrical rhythms during listening to music and how cognition and acoustic structural aspects of songs influence that interaction. We focused on tempo as a structural feature of songs, since tempo is a major determinant of physiological responses to music, and on familiarity and randomization of phase of local spectra of known and unknown songs for cognition. Our results indicated an overall increase in the degree of synchronization among cardiorespiratory variables (Heart rate (RR), systolic and diastolic blood pressure (SBP, DBP), respiration) and between cardiorespiratory and cerebral (EEG) oscillations during all songs. We also observed a marked decrease in respiratory frequency bandwidth and increase in respiratory rate while listening to songs, and slow song produced the most periodic breathing. Compared with slow tempo, during fast song, DBP and cerebral oscillations became less synchronized with high frequency components of RR suggesting that the processes causing the previously known reduction in vagal activity with increase in tempo also may have caused the decrease in these synchronizations. Cognition of songs affected the SBP coherencies the most. DBP was synchronized with respiration more than all other measured variables in response to auditory stimuli. Results indicate an overall increase in the degree of synchronization among a variety of cerebral electrical and autonomically driven cardiovascular rhythms. It is possible that this significant increase in synchronizations underlies the widely reported pleasurable and palliative effects of listening to music.
Keywords: Cortical Synchronization; Cognition; mužské pohlaví; Male; korová synchronizace; Female; hudba; Humans; autonomní nervový systém; Autonomic Nervous System; sluchová percepce; lidé; dýchání; ženské pohlaví; kognice; mladiství; krevní tlak; Young Adult; Adolescent; Auditory Perception; mladý dospělý; Heart; Blood Pressure; dospělí; Adult; srdce; Healthy Volunteers; Music; zdraví dobrovolníci pro lékařské studie; Respiration